Trauma Roundtable: Management of an Ankle Fracture-Dislocation in an Elderly Woman with Medial Skin Compromise. Issue 3 (July 2017) - Cloutier, Dagan; Eagen, Caitlin; Hull, Jonathan; Paul, Keith W.; Riehl, John T.
Abstract : The purpose of the JOPA Roundtable discussions is to give orthopaedic PAs insight on how each participating editorial board member would treat certain clinical scenarios in their current practice. For this Trauma Roundtable, JOPA Editor Dagan Cloutier, PA-C, asked JOPA editorial board members with expertise in orthopaedic trauma questions about the following case: an 84-year-old woman presented to the emergency department with a right ankle fracture-dislocation and skin compromise on the medial aspect of the ankle.